2003
DOI: 10.1152/ajpcell.00095.2003
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function correlation in airway smooth muscle adapted to different lengths

Abstract: Airway smooth muscle is able to adapt and maintain a nearly constant maximal force generation over a large length range. This implies that a fixed filament lattice such as that found in striated muscle may not exist in this tissue and that plastic remodeling of its contractile and cytoskeletal filaments may be involved in the process of length adaptation that optimizes contractile filament overlap. Here, we show that isometric force produced by airway smooth muscle is independent of muscle length over a twofol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
111
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(127 citation statements)
references
References 20 publications
15
111
0
1
Order By: Relevance
“…Other structures include myosin filaments, actin filaments, cytoskeletal cross-linker molecules, cytosolic dense bodies, membrane adhesion plaques and cell-cell connections [55,185]. There is ample evidence for each of these candidates to be somehow involved in the response to external perturbation [168,174,[186][187][188][189][190][191].…”
Section: In Vitro Behaviour Of Asmmentioning
confidence: 99%
See 1 more Smart Citation
“…Other structures include myosin filaments, actin filaments, cytoskeletal cross-linker molecules, cytosolic dense bodies, membrane adhesion plaques and cell-cell connections [55,185]. There is ample evidence for each of these candidates to be somehow involved in the response to external perturbation [168,174,[186][187][188][189][190][191].…”
Section: In Vitro Behaviour Of Asmmentioning
confidence: 99%
“…By examining the details of length-dependent properties of ASM, including adapted and nonadapted isometric force, shortening velocity, power output, rate of adenosine tiphosphate utilisation and change in myosin filament density (or filament mass), KUO et al [188], QI et al [192] and HERRERA and co-workers [192][193][194][195] have provided evidence that length adaptation in ASM involves changes in the number of contractile units in series and in parallel. They also showed that externally applied strain on ASM in the relaxed state led directly to partial disassembly of the myosin filaments [168], thus providing an explanation for the strain-induced inhibition of muscle force, which could underlie the phenomenon of deepinspiration-induced bronchoprotection, as discussed in the previous section.…”
Section: In Vitro Behaviour Of Asmmentioning
confidence: 99%
“…One of the most obvious differences is that smooth muscle lacks the highly regular organisation of contractile filaments which give rise to the banded structure in striated muscle. In addition, various types of smooth muscles are able to generate the same maximum isometric force over a wide range of lengths given time to adapt (Pratusevich et al, 1995;Kuo et al, 2003;Herrera et al, 2005;Martinez-Lemus et al, 2008;Tuna et al, 2011). This is in sharp contrast to striated muscle where the maximum isometric force is associated with a particular length (Gordon et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that smooth muscle length adaptation is connected to a structurally and 'plastic-like' mechanism of contractile and other cytoskeletal filaments (Kuo et al, 2003;Herrera et al, 2005;Seow, 2005;van den Akker et al, 2010). Both actin and myosin polymerise and depolymerise rapidly in response to activation (Mehta & Gunst, 1999;Herrera et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation